Respiratory drive: a journey from health to disease - Dimitrios Georgopoulos; Maria Bolaki; Vaia Stamatopoulou; Evangelia Akoumianaki (Journal of Intensive Care)
Abstract Respiratory drive is defined as the intensity of respiratory centers output during the breath and is primarily affected by cortical and chemical feedback mechanisms. During the involuntary act of breathing, chemical feedback, primarily mediated through CO2, is the main determinant of respiratory drive. Respiratory drive travels through neural pathways to respiratory muscles, which execute the breathing process and generate inspiratory flow (inspiratory flow-generation pathway). In a healthy state, inspiratory flow-generation pathway is intact, and thus respiratory drive is satisfied by the rate of volume increase, expressed by mean inspiratory flow, which in turn determines tidal volume. In this review, we will explain the pathophysiology of altered respiratory drive by analyzing the respiratory centers response to arterial partial pressure of CO2 (PaCO2) changes. Both high and low respiratory drive have been associated with several adverse effects in critically ill patients. Hence, it is crucial to understand what alters the respiratory drive. Changes in respiratory drive can be explained by simultaneously considering the (1) ventilatory demands, as dictated by respiratory centers activity to CO2 (brain curve); (2) actual ventilatory response to CO2 (ventilation curve); and (3) metabolic hyperbola. During critical illness, multiple mechanisms affect the brain and ventilation curves, as well as metabolic hyperbola, leading to considerable alterations in respiratory drive. In critically ill patients the inspiratory flow-generation pathway is invariably compromised at various levels. Consequently, mean inspiratory flow and tidal volume do not correspond to respiratory drive, and at a given PaCO2, the actual ventilation is less than ventilatory demands, creating a dissociation between brain and ventilation curves. Since the metabolic hyperbola is one of the two variables that determine PaCO2 (the other being the ventilation curve), its upward or downward movements increase or decrease respiratory drive, respectively. Mechanical ventilation indirectly influences respiratory drive by modifying PaCO2 levels through alterations in various parameters of the ventilation curve and metabolic hyperbola. Understanding the diverse factors that modulate respiratory drive at the bedside could enhance clinical assessment and the management of both the patient and the ventilator.